IMPLEMENTASI KERJA SAMA INDONESIA - TIONGKOK DALAM PEMBANGUNAN INFRASTRUKTUR TRANSPORTASI LAUT DI PELABUHAN KUALA TANJUNG - RANIA VICCIE ADNYAHAYU, (2022)
Port is the main portal in the national maritime sector so the existence of port is very important for every country, including Indonesia. Efforts to optimize the function of ports require quality infrastructure that meets standards, but in fact the quality of ports in Indonesia is still far from that level, so development and follow-up on this infrastructure are needed. As an effort to improve the quality of ports, Indonesia cooperates with China to build a national port, one of which is the Kuala Tanjung Port. However, in terms of cooperation between Indonesia and China, it has not run perfectly and has several obstacles in the process, therefore the cooperation between Indonesia and China in the construction of this port has been delayed. This study explains the explanation of the bilateral cooperation and foreign direct investment. This study uses a qualitative method with descriptive analysi. The results of this research show that the cooperation between Indonesia and China can still be implemented and results in the transfer of technology.